Application of non-thermal plasma in medicine: a bibliometric and visualization analysis - Guo, Linna; Yan, Miao; Gong, Hui; Zou, Ziang; Henningsen, Anders (Frontiers in Physics, 2023)
Non-thermal plasma has been widely studied in medicine due to its beneficial effect with low thermal or other damages. Numerous medical research studies have been conducted using non-thermal plasma devices; yet, to date, there is no report summarizing this field as a whole. In this study, we aim to perform a bibliometric analysis to assess the state of research, current research priorities, and emerging trends in non-thermal plasma medicine over the last two decades. Publications related to non-thermal plasma medicine (2002–2022) were searched in Web of Science core collection. Bibliometric analysis and visualization was then performed using R-Bibliometrix and CiteSpace. A total of 725 publications related to non-thermal plasma were identified. The annual number of publications has increased continuously over the past two decades. n the field of non-thermal plasma medicine, Germany, China and the United States dominated. Of all institutions, Leibniz Institute for Plasma Science and Technology published the most papers. The journal with highest citation was JOURNAL OF PHYSICS D-APPLIED PHYSICS. Bekeschus Sander published the highest H-value of articles. “Inactivation”, “Apoptosis”, “Chronic Wound” is the primary focus area of non-thermal plasma medicine, “Differentiation”, “Water”, “Gene Expression” and “Cell Death” were the main keywords of the new research hotspots. In this study, bibliometric methods were used to analyze current research priorities and trends in non-thermal plasma medicine and to identify the countries, institutions, authors, and journals with the greatest influence in the field to enhance collaboration and learning.